UPAYA MENINGKATKAN KESEHATAN ANAK SEKOLAH MELALUI EDUKASI TENTANG PENTINGNYA SARAPAN PAGI DAN PEMERIKSAAN KESEHATAN SECARA BERKALA - prijatni, ida; Jamhariyah, Jamhariyah; Prasetyo, Hendro; Bachri, Syaiful (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
School children play a crucial role in determining the future of a nation. Safeguarding children equates to safeguarding the nation's future. The primary focus of national development is its people; hence, thorough preparation for the younger generation is of paramount importance. Breakfast, the act of consuming food in the morning between 06:00 and 10:00, plays a vital role in meeting 15-30% of daily nutritional needs (Putra, 2022). Research indicates that regular breakfast not only ensures adequate nutrition but also enhances concentration in learning and absorption of lessons at school (Novianti et al., 2022). Furthermore, the habit of having breakfast influences the stability of blood glucose levels, affecting learning readiness and children's well-being (Rahmiwati, 2014). However, field realities indicate that many children skip breakfast, opting instead for school snacks with inadequate nutritional value. Education about the importance of breakfast and regular health checkups emerges as a relevant solution. This approach is expected to transform children's knowledge, attitudes, and behaviors (Novianti et al., 2022). Collaboration among families, schools, and communities is key to achieving this objective. Proper education can motivate children to adopt a positive breakfast routine. With an understanding of proper nutrition and regular health care, children will grow better, leading to the nation's progress